PERSEPSI WAJIB PAJAK ATAS PENGENAAN PAJAK PENGHASILAN (WAJIB PAJAK ORANG PRIBADI YANG MEMILIKI USAHA DI KOTA BANJARMASIN) - Nadila Fitria Ramadhani; Doni Stiadi; Muzdalifah (Universitas Lambung Mangkurat, 2021)
Considering that the opinion of the tax user community on the obligation to pay income tax can affect the compliance of the community to fulfill the obligation to pay taxes and public compliance is an important factor in increasing the results of tax revenue, it is necessary to conduct a study on the reasons that influence the opinion of the tax user community on the obligation to pay taxes. income and community compliance in fulfilling the obligation to pay taxes, especially for individual taxpayers.